EFFECTIVENESS OF PROVIDING EDUCATION RELATED TO FATHER INVOLVEMENT AND SUPPORT IN THE 1000 FIRST DAYS OF LIFE IN EARLY PREVENTION OF STUNTING IN JEBRES VILLAGE - Margatot, Didik Iman; Tendean, Angelia Friska; Permatasari, Putri Intan; Wisanggeni, Oni Wisanggeni (Fakultas Keperawatan, Universitas Klabat, 2024)
The problem that is currently still often recurring is related to nutritional problems or better known as stunting. Stunting or in short is a global nutritional problem that often occurs in children under 5 years of age. Children under 5 years of age are categorized as stunting / short if they have a z score below -2 SD. The purpose of this study was to increase fathers' knowledge in providing support for fulfilling toddler nutrition in 1000 first days of life and to see the effectiveness of fathers' support in preventing stunting in toddlers. This research method uses a Quasi experiment using the Onegroup Pretest-Posttest design. The results of the study showed a significant difference in value before and after the intervention, with a p-value of 0.001 at a 95% confidence level.. The conclusion in this study is that there is effectiveness in providing education in increasing a father's knowledge, attitudes, and support in preventing stunting in the first 1000 days of life Permasalahan yang saat ini sering terjadi secara berulang adalah terkait masalah gizi atau lebih dikenal dengan istilah stunting. Stunting merupakan masalah gizi global yang sering terjadi pada anak di bawah usia 5 tahun. Anak usia dibawah 5 tahun dikategorikan stunting/pendek jika mempunyai nilai skor z dibawah -2 SD. Tujuan penelitian ini adalah untuk meningkatkan pengetahuan ayah dalam memberikan dukungan pemenuhan gizi balita pada 1000 Hari Pertama Kehidupan (HPK) dan melihat efektivitas dukungan ayah dalam mencegah stunting pada balita. Metode penelitian ini menggunakan Quasi eksperimen dengan desain Onegroup Pretest-Posttest. Hasil penelitian menunjukkan adanya perbedaan nilai yang signifikan sebelum dan sesudah intervensi, dengan p-value sebesar 0,001 pada tingkat kepercayaan 95%. Kesimpulan dalam penelitian ini adalah terdapat efektivitas pemberian pendidikan dalam meningkatkan pengetahuan seorang ayah, sikap, dan dukungan dalam mencegah stunting pada 1000 HPK.